Decentralized Frequency Control of Microgrids with Constraints: An LMI Approach - Al-Karsani, Ahmed Saad; Khanbaghi, Maryam; Zarghami, Mahyar (North American Power Symposium (Online), 2024)
With the integration of Renewable Energy Sources (RES) and subsequent formation of microgrids (MGs), reliable control schemes will be required to deal with increased vulner-ability to instability issues. Such issues can be alleviated within Networked MG (NMG) frameworks, but the variable nature of RES within NMGs can lead to operation challenges. One of the challenges arising that is not commonly addressed relates to meeting grid or network codes, such as frequency ride-through (if it is within a predefined range) to avoid cascading trips from power imbalances. To address such a challenge, this paper proposes a decentralized robust secondary frequency control using an LMI-based control strategy. The scheme incorporates a frequency deviation constraint using a bounded Lyapunov function condition to ensure that the deviation is within a predefined value. The proposed scheme has been validated in MATLAB/Simulink©, showing that frequency deviation can be constrained whilst achieving secondary level regulation.